Exploring the link between principal leadership and family engagement across elementary and middle school. (February 2021) - Smith, Tyler E.; Reinke, Wendy M.; Herman, Keith C.; Sebastian, James
Abstract: As leaders in the school, principals play an important role in fostering family engagement. Unfortunately, little is known about specific aspects of leadership that promote family engagement. Collegial leadership, an aspect of principal leadership that promotes organizational health via trusting relationships and a sense of community, may be particularly useful to understanding how principals influence family engagement. Drawing on data from two randomized controlled trials evaluating the effects of teacher training in universal classroom management practices, the current study explores the relationship between teacher reports of family engagement and principal collegial leadership. Participants included 3208 students and 207 teachers across 18 elementary and middle schools in the Midwest United States. Utilizing hierarchical linear modeling, results revealed a significant positive relationship between family engagement and overall collegial leadership in addition to specific collegial leadership practices/characteristics. Further, baseline collegial leadership predicted increased end-of-year family engagement when controlling for baseline family engagement, developmental context, intervention status, and student-level characteristics. Overall, results provide empirical evidence for an important link between principal leadership practices and family engagement. Albeit promising, more research is needed to identify and explain the particular mechanisms by which principal collegial leadership may promote family engagement.